LACAME 2004 Proceedings of the 9th Latin American Conference on the Applications of the Mössbauer Effect, (LACAME 2004) held in Mexico City, Mexico, 19-24 September 2004 - Mercader, R.C.; Gancedo, J.R.; Cabral Prieto, A.; Baggio-Saitovitch, E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
Proceedings of the 9th Latin American Conference on the Applications of the Mössbauer Effect, LACAME 2004, held in Mexico City, Mexico, 19-24 September 2004. Researchers and graduate students interested in the Mössbauer Effect and its applications will find this volume indispensable. The volume presents the most recent developments in the methodology of Mössbauer spectroscopy. Reprinted from Hyperfine Interactions (HYPE) Volume 161, 1-4.
Effect of the Calcination Atmosphere on the Structural Properties of the Reduced Fe/SiO2 System -- NMR and Mössbauer Study of Al2O3-Eu2O3 -- From Ore to Tool — Iron Age Iron Smelting in the Largest and Oldest Meteorite Crater in the World -- Hydrometallurgical Extraction of Zinc and Copper — A 57Fe-Mössbauer and XRD Approach -- Magnetic and Mössbauer Studies of Quaternary Argentine Loessic Soils and Paleosols -- Recovery of Heavy Minerals by Means of Ferrosilicon Dense Medium Separation Material -- Structural and Electronic Properties Study of Colombian Aurifer Soils by Mössbauer Spectroscopy and X-ray Diffraction -- Vickers Microhardness and Hyperfine Magnetic Field Variations of Heat Treated Amorphous Fe78Si9B13 Alloy Ribbons -- Mössbauer and X-Ray Diffraction Investigations of a Series of B-Doped Ferrihydrites -- Study of Malayaite and Malayaite Cobalt Pigment -- Study on Stereochemical Activity of Lone Pair Electrons in Sulfur and Halogen Coordinated Antimony(III) Complexes by 121Sb Mössbauer Spectroscopy -- Cationic Order in Double Perovskite Oxide, Sr2Fe1?x ScxReO6 (x = 0.05, 0.1) -- Synthesis of Calcium Telluride as a Possible Mössbauer Source -- On the Rust Products Formed on Weathering and Carbon Steels Exposed to Chloride in Dry-Wet Cyclical Processes -- Design and Construction of an Autonomous Control System for Mössbauer Spectrometry -- ILEEMS: Methodology and Applications to Iron Oxides -- Ferrimagnetic to Paramagnetic Transition in Magnetite: Mössbauer versus Monte Carlo -- Mössbauer Investigation of Fe-Mn-Cu Nanostructured Alloys Obtained by Ball Milling -- Study of the Morin Transition in Pseudocubic ?-Fe2O3 Particles -- Anelastic Relaxation Mechanisms Characterization by Mössbauer Spectroscopy -- Comparative Study by MS and XRD of Fe50Al50 Alloys Produced by Mechanical Alloying, Using Different Ball Mills -- First Principles Determination of Hyperfine Parameters on fcc-Fe8X (X=C, N) Arrangements -- Magnetic and Structural Properties of the Mechanically Alloyed Nd2(Fe100?x Nbx)14B System -- Mechanosynthesis of YIG and GdIG: A Structural and Mössbauer Study -- Mössbauer Spectroscopy, Dilatometry and Neutron Diffraction Detection of the ?-Phase Fraction in Fe-Mn Shape Memory Alloys -- Effects of Hole-Doping on Superconducting Properties in MgCNi3 and its Relation to Magnetism -- Influence of Electron Delocalization on the Magnetic Properties of Iron Ludwigite Fe3O2BO3.
Keywords: Solid state physics; Spectroscopy; Microscopy; Solid State Physics; Spectroscopy and Microscopy